2010
DOI: 10.1021/jo101779v
|View full text |Cite
|
Sign up to set email alerts
|

Mannosazide Methyl Uronate Donors. Glycosylating Properties and Use in the Construction of β-ManNAcA-Containing Oligosaccharides

Abstract: Mannosazide methyl uronate donors equipped with a variety of anomeric leaving groups (β- and α-S-phenyl, β- and α-N-phenyltrifluoroacetimidates, hydroxyl, β-sulfoxide, and (R(s))- and (S(s))-α-sulfoxides) were subjected to activating conditions, and the results were monitored by (1)H NMR. While the S-phenyl and imidate donors all gave a conformational mixture of anomeric α-triflates, the hemiacetal and β- and α-sulfoxides produced an oxosulfonium triflate and β- and α-sulfonium bistriflates, respectively. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 76 publications
2
54
0
Order By: Relevance
“…α‐Thioglycosides and analogous α‐sulfoxides of S ‐phenyl mannoazide uronate donors were also shown to exist primarily in the 1 C 4 confirmation, as opposed to the corresponding β‐thioglycoside/sulfoxide anomers that adopt a 4 C 1 chair in line with the observations made for xylopyranosyl sulfoxides.…”
Section: Stereochemical Preferences Of Glycosyl Sulfoxidessupporting
confidence: 72%
“…α‐Thioglycosides and analogous α‐sulfoxides of S ‐phenyl mannoazide uronate donors were also shown to exist primarily in the 1 C 4 confirmation, as opposed to the corresponding β‐thioglycoside/sulfoxide anomers that adopt a 4 C 1 chair in line with the observations made for xylopyranosyl sulfoxides.…”
Section: Stereochemical Preferences Of Glycosyl Sulfoxidessupporting
confidence: 72%
“…56 On gaining an insight into the reaction mechanism, it was concluded that when thiophenyl donor 37 is activated in the presence of diphenyl sulfoxide and triflic anhydride, anomeric triflate 38 is formed (Scheme 5). The latter exists as an interchangeable mixture of conformers with the 1 C 4 chair as the predominant species.…”
Section: Effect Of the Glycosyl Donormentioning
confidence: 99%
“…It is challenging to form this linkage as it is thermodynamically less stable than the corresponding 1,2‐ trans linkage due to the anomeric effect and the steric hindrance posted by the C2 substituent in glycosylation. The van der Marel group developed a series of 2‐azido mannosyluronate donors bearing various anomeric leaving groups including thioether, sulfoxide and trifluoroacetimidate (donors 170 – 176 ) . Under the pre‐activation protocol, all these glycosyl donors gave good 1,2‐ cis selectivities.…”
Section: Inductive Effect From Electron Withdrawing Protective Gromentioning
confidence: 99%